2015
DOI: 10.1016/j.apsusc.2015.06.065
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nanoparticles size on photocatalytic and antimicrobial properties of Ag-Pt/TiO2 photocatalysts

Abstract: Please cite this article as: A. Zielińska-Jurek, Z. Wei, I. Wysocka, P. Szweda, E. Kowalska, The effect of nanoparticles size on photocatalytic and antimicrobial properties of Ag-Pt/TiO 2 photocatalysts, Applied Surface Science (2015), http://dx.A c c e p t e d M a n u s c r i p t Highlights  Enhanced photocatalytic activity under visible light for bimetallic Ag-Pt/TiO 2 was observed  Phenol was removed efficiently after 60 min. irradiation under Vis  Most active sample contains fine Pt (1-3nm) on TiO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(62 citation statements)
references
References 23 publications
3
58
0
Order By: Relevance
“…Moreover, the existence of particles would induce scattering effect which is observed in the DRS spectra. By applying bare titania as reference (Figure 4b), the plasmon bands with a maxima at around 400 nm was clear for single silver modified titania, which is comparable with the literature (20)(21). Therein, it was also proposed that the source of titania would shift the maxima plasmon bands for silver NPs.…”
Section: Characterization Of the Photocatalystssupporting
confidence: 84%
See 3 more Smart Citations
“…Moreover, the existence of particles would induce scattering effect which is observed in the DRS spectra. By applying bare titania as reference (Figure 4b), the plasmon bands with a maxima at around 400 nm was clear for single silver modified titania, which is comparable with the literature (20)(21). Therein, it was also proposed that the source of titania would shift the maxima plasmon bands for silver NPs.…”
Section: Characterization Of the Photocatalystssupporting
confidence: 84%
“…Therefore, the presence of ruthenium(II) was confirmed in all Ru II CP2-contained samples, based on this absorption. For plasmonic metal nanoparticles, usually, broad absorption in the range of 400-800 nm is observed by their localized surface plasmon resonance, especially in the case of nanoparticles possessing broad distribution of sizes and shapes (21). Moreover, the existence of particles would induce scattering effect which is observed in the DRS spectra.…”
Section: Characterization Of the Photocatalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown that photoactivity of P25 exceeds that of anatase in several reaction systems [41,42]. Previously, we have also reported that TiO 2 P25, which is a mixture of anatase and rutile phases exhibited higher efficiency of phenol, pyridine and 4-heptanone degradation compared to commercial anatase particles TiO 2 ST-01 and anatase obtained from titanium isopropoxide (TIP) and titanium butoxide (TBT) hydrolysis in aqueous phase [43,44]. Therefore, the lower photocatalytic activity of BaFe 12 O 19 /SiO 2 /TiO 2 _2 nanocomposite results from the properties of the photocatalytic layer instead of the magnetic core behavior.…”
Section: Discussionmentioning
confidence: 85%